Some Aspects of Micro-HPP Utilization in the Republic of Moldova - Ambros T.; Ursatii N. (Problems of the Regional Energetics)
The hydrografic network in the Republic of Moldova and some historical aspects of micro-Hydro Power Plants (mHPP) on the country territory have been described. There are presented some models of micro hydro damless samples developed by the Technical University of Moldova.